2013
DOI: 10.1074/jbc.m113.492595
|View full text |Cite
|
Sign up to set email alerts
|

Control of Histone H3 Lysine 9 (H3K9) Methylation State via Cooperative Two-step Demethylation by Jumonji Domain Containing 1A (JMJD1A) Homodimer

Abstract: Background: JMJD1A specifically demethylates mono-and dimethyl-histone H3K9. Results: Two active sites of JMJD1A homodimer cooperatively demethylate dimethylated H3K9. Conclusion: Homodimerization of JMJD1A is essential for appropriate control of histone methylation state. Significance: The novel demethylation mechanism of JMJD1A will help in understanding the histone code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Overall, knock down of methylation related enzymes appeared to enhance proliferation while loss of demethylases, in particular the H3K9 demethylases KDM4s/ KDM3s, decreased growth in LNCaP-abl. Importantly, this was not due to shRNA off-target effects as a similar phenotype with both different shRNA and CRISPR/Cas9 was [14,53]. Overexpression of ΔZF KDM3B may thus inactivate the endogenous KDM3B.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, knock down of methylation related enzymes appeared to enhance proliferation while loss of demethylases, in particular the H3K9 demethylases KDM4s/ KDM3s, decreased growth in LNCaP-abl. Importantly, this was not due to shRNA off-target effects as a similar phenotype with both different shRNA and CRISPR/Cas9 was [14,53]. Overexpression of ΔZF KDM3B may thus inactivate the endogenous KDM3B.…”
Section: Discussionmentioning
confidence: 91%
“…JMJD1A regulates gene expression through H3K9 demethylation ( 1 , 2 ). To assess global gene regulation by JMJD1A in an effort to identify how it regulates proliferation or survival of prostate cancer cells, we performed array-based gene expression analyses of Rv1 cells expressing JMJD1A shRNA.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that KDM3A was distinct from other Jumonji C family members in both its structure and function. KDM3A forms a homodimer through its catalytic domains, and catalyses removal of H3K9 methylation via a two-step process in which two active sites of the dimer are crucial for the enzymatic activity 51 . This reaction mechanism is totally different from catalytic processes of other JumonjiC H3K9 demethylases such as PHF8 and KIAA1718, which neither form a homodimer nor catalyse successive two-step methylation 52 .…”
Section: Discussionmentioning
confidence: 99%